REFORMASI AGRARIA DALAM PERSPEKTIF PERLINDUNGAN LINGKUNGAN HIDUP - Wahidin, Samsul (Jurnal Cakrawala Hukum, 2017)
The aggregate sector is one of the most complex social issues. This is in line with population growth and the need for natural resources, especially land. The settlement of Agraria disputes to seek legal certainty which has long been untouchable for the settlement of the problem. While the solution to the problem tends to keep pace with the ongoing changes. The solution tends to be temporary. In the case of a solid foundation as a basis for completion, not only for the present but for the future. As a result of these limitations, the various rules that exist and serve as the basis of the law are lagging behind by the reality of society. A far-reaching orientation is from an environmental perspective. As a result of these limitations to this orientation, environmental issues tend to be ignored. Here, the urgency of structuring must start from the beginning, with emphasis on the mindset of the community on the problem of aggregation, in the perspective of lasting environmental protection. It takes a synergy between the question of aggregation on the one hand and the need for an environment-based management orientation on the other side.